RELATIONSHIP BETWEEN COPING MECHANISM TO LEVEL OF STRESS OF HOUSEWIFE - Kusniyatun, Umi; Astuti, Fitri Budi; Bintoro, Wahyu (JURNAL ILMU KEPERAWATAN INDONESIA (JIKI), 2014)
Background : A housewife is a profession that often considered easy to do , but a housewife is frequently experiencing stress. One factor that influenced the level of stress of housewife is coping mechanism, that is a way to adapt with stressor, especially in addressing fatigue, boredom, and bustle in completing householdworks. Purpose : To know the relationship between coping mechanism and level of stress of housewife. Methods : The research use descriptive correlational with cross-sectional approach. Population of the research is housewives of Mancasan Village RW III, Baki, Sukoharjo . The samples are 40 respondents who are taken by using nonprobability sampling technique with a purposive sampling . Data analysis of the research is Kendall Tau. Results : The results of the research indicated that most housewives applied adaptive coping mechanism, as 32 respondents (80%) and who suffered mild stress is 27 respondents (67.5 %). Conclusion : There is a significant correlation between coping mechanism and stress level of housewife in Mancasan Village RW III, Baki, Sukoharjo. It is proved with statistical result of Kendall Tau with significance of 0.02 < 0.05.